Big Data Benchmarks, Performance Optimization, and Emerging Hardware 4th and 5th Workshops, BPOE 2014, Salt Lake City, USA, March 1, 2014 and Hangzhou, China, September 5, 2014, Revised Selected Papers - Zhan, Jianfeng; Han, Rui.; Weng, Chuliang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the thoroughly revised selected papers of the 4th and 5th workshops on Big Data Benchmarks, Performance Optimization, and Emerging Hardware, BPOE 4 and BPOE 5, held respectively in Salt Lake City, in March 2014, and in Hangzhou, in September 2014. The 16 papers presented were carefully reviewed and selected from 30 submissions. Both workshops focus on architecture and system support for big data systems, such as benchmarking; workload characterization; performance optimization and evaluation; emerging hardware.
Architecture and system support for big data systems -- Benchmarking -- Workload characterization -- Performance optimization and evaluation -- Emerging hardware.
Keywords: Data mining; Information storage and retrieval; Data Mining and Knowledge Discovery; Information Storage and Retrieval